Integration of Affective Evaluation in Arabic Language Learning: Theoretical and Conceptual Analysis - Safitri, Zuliyah; Hanifah, Umi (STIQ Amuntai, 2025)
The affective dimension in Arabic language learning has often been overlooked in favor of cognitive outcomes, despite its importance in shaping students’ values, attitudes, and motivation, especially within Islamic education contexts. This study aims to explore the theoretical and conceptual framework of affective evaluation and its integration into Arabic learning. Using a qualitative approach with library research methods, the study analyzes key educational and psychological literature to identify principles, instruments, and implementation strategies for affective assessment. The findings indicate that affective evaluation, grounded in Bloom’s taxonomy, plays a significant role in fostering students’ moral and emotional development. However, challenges such as lack of teacher training, limited time, and absence of contextualized instruments hinder its application. To address this, the study proposes strategies including reflective activities, behavioral observation, and value-based projects to embed affective assessment into teaching practices. This conceptual analysis contributes to filling a gap in Arabic education research by offering practical guidelines for character-oriented evaluation. Future empirical studies are needed to validate these models in real classroom settings.